PENDIDIKAN AGAMA ISLAM (PAI) MULTIKULTURAL PERSPEKTIF PEMBELAJARAN INTEGRATIF - Hakim, Lukman; Haris, Abdul (TA'LIM : Jurnal Studi Pendidikan Islam, 2024)
Abstract: This paper examines the multicultural Islamic education as an integrative learning model that combines science and religion. According to its content, multiculturalism examines the diversity of nations, ethnicities, skin colors, languages, religions and other diversity that lies in the social reality of human life as verses of Allah which are kauniyah. Meanwhile, Islamic education studies the normativity of Islamic teachings and the historical dimensions contained in the Holy Qur’an as the verses of Allah which are qauliyah. The learning of these two scientific fields is both a process of searching for the truth which refers to Allah as the epicenter of truth and the source of knowledge. Based on the concept of integrative learning put forward by Islamic and Western thinkers, the multicultural Islamic education is in the interdisciplinary relationship pattern, namely the integration between general science and religious science. The multicultural Islamic education as integrative learning is reflected in the objectives, materials, methods, media and learning resources and evaluation that are integrated each other in forming an integral religious competence of students, namely: integration between worldly and hereafter elements, between spiritual and intellectual dimensions, between the personal and social domains in the context of building harmony in the life of the school community, society and the Indonesian nation which is pluralistic in all its aspects.